Cooperative answering of queries based on hierarchical decision attributes - Raś, Zbigniew W.; Zhang, Xin (Computer Assisted Methods in Engineering and Science, 2022)
This paper considers decision systems (see [6]) with decision attributes which are hierarchical. Atomic queries are built only from values of decision attributes. Queries are constructed from atomic queries the same way as we construct terms in logic using functors {+, *, -.}. Negation symbol "-." is only used on the atomic level. Queries are approximated by terms built from values of classification attributes. We only consider rule-based classifiers as the approximation tool for queries. When a user query fails, then the cooperative module of the query answering system (QAS) constructs its smallest generalization which does not fail and which is approximated by rules of the highest confidence discovered by the classifier. Two interpretations of queries are proposed: user-based and system-based. They are used to introduce the precision and recall of QAS. The implementation of QAS follows system-based interpretation. Automatic indexing of music by instruments and their types is an example of the application area for the proposed approach.